Fish, fun & feedback. IN City Sense [column] - Alcazaren, Paulo (2007)
I've gotten a fair amount of e-mail the past week on the "21 places I love in the city" two weeks ago. A number of friends and relatives also told me that this article was a good breather from my usual rants and scenarios of urban gloom and doom. So these next few weeks, I'll offer more of the positive and hold off my ranting till September. I was traveling again the past few weeks and found other places for Filipinos to discover in their own country.